Functional outcomes of modified Bristow procedure in recurrent shoulder dislocation - Khadim Khawaja; Yasir Mohib; Muhammad Younus Khan Durrani; Naveed Muhammad Juman; Ahmed Abdul Habib; Pervaiz Hashmi (Journal of the Pakistan Medical Association, 2021)
The glenohumeral joint is the most mobile in humans. Of all joints 50% dislocations involve the shoulder, mostly young males. When the first dislocation occurs under 20 years old the risk for recurrent instability increases to 90%. Many techniques are available to reduce and stabilize the glenohumeral joint in cases of anterior dislocations one of which is the famous Bristow’s procedure, originally described in 1954 by Laterjet. The purpose of this study was to determine the Functional Outcomes of Modified Bristow procedure. This retrospective review conducted at Aga Khan University Hospital Karachi from Jan 2000- Dec 2015, comprising patients who underwent modified Bristow procedure. 70 patients were recruited in the study who underwent modified Bristow procedure. Continuous...